The effect of aspirin on lumbar degeneration: an imaging-based study - Niu, Haiyun; Zu, Feiyu; Shang, Zhenguo; Gao, Ze; Miao, Dazhuang; Zhang, Di (Frontiers in Surgery, 2024)
PurposeThis study aims to investigate how aspirin influences lumbar degeneration by analyzing the effect of aspirin on patients with low back pain (LBP) and concurrent atherosclerosis.MethodsUsing 1:1 nearest neighbor matching based on propensity score matching (PSM), 73 patients who regularly took aspirin were assigned to the aspirin group, while another 73 patients who did not take aspirin formed the control group. Radiographs were used to measure lumbar lordosis (LL) and intervertebral height index (IHI). Subcutaneous fat tissue thickness (SFTT), paravertebral muscle fat infiltration area (%FIA), cartilage endplate (CEP) Modic changes, and modified Pfirrmann grading scores were performed based on lumbar MRI.ResultsAfter PSM analysis, confounders between the aspirin and control groups were balanced. A total of 73 pairs of patients were analyzed in this study. The aspirin group showed lower SFTT(L1/2) and a reduced incidence of CEP Modic changes, compared to the control group (both P < 0.05). Additionally, the %FIA and Pfirrmann scores were lower in the aspirin group, particularly in the upper lumbar spine (both P < 0.05). No significant differences were observed in LL and IHI between the aspirin and control groups.ConclusionIn summary, conservative treatment with aspirin protects against upper lumbar spine degeneration, although its effect on the lower lumbar spine is less pronounced.